Suppression of Cisplatin-Induced Vomiting by Cannabis sativa in Pigeons: Neurochemical Evidences - Ullah, Ihsan; Subhan, Fazal; Alam, Javaid; Shahid, Muhammad; Ayaz, Muhammad (Frontiers in Pharmacology, 2018)
Cannabis sativa (CS, family Cannabinaceae) has been reported for its antiemetic activity against cancer chemotherapy-induced emesis in animal models and in clinics. The current study was designed to investigate CS for potential effectiveness to attenuate cisplatin-induced vomiting in healthy pigeons and to study the impact on neurotransmitters involved centrally and peripherally in the act of vomiting. High Performance Liquid Chromatography system coupled with electrochemical detector (HPLC-ECD) was used for the quantification of neurotransmitters 5-hydroxytryptamine (5HT), dopamine (DA) and their metabolites; Di-hydroxy Phenyl Acetic acid (Dopac), Homovanillic acid (HVA) and 5-hydroxy indole acetic acid (5HIAA) centrally in specific brain areas (area postrema and brain stem) while, peripherally in small intestine. Cisplatin (7 mg/kg i.v.) induce emesis without lethality across the 24 hr observation period. CS hexane fraction (CS-HexFr; 10 mg/kg) attenuated cisplatin induced emesis ~ 65.85 % (P < 0.05); the reference anti-emetic drug, metoclopramide (MCP; 30 mg/kg), produced ~ 43.90 % reduction (P < 0.05). At acute time point (3rd h), CS-HexFr decreased (P < 0.001) the concentration of 5HT and 5HIAA in the area postrema, brain stem and intestine, while at 18th h (delayed time point) CS-HexFr attenuated (P < 0.001) the upsurge of 5HT caused by cisplatin in the brain stem and intestine and dopamine in the area postrema. CS-HexFr treatment alone did not alter the basal neurotransmitters and their metabolites in the brain areas and intestine except 5HIAA and HVA, which were decreased significantly. In conclusion the anti-emetic effect of CS-HexFr is mediated by anti-serotonergic and anti-dopaminergic components in a blended manner at the two different time points i.e 3rd hr and 18th hr in pigeons.